Effect of chronic treatment with Clomipramine on food intake, macronutrient selection and body weight gain in rats - Calegari, Leonardo (2007)
Long-term treatment with clomipramine (CMI), a tricyclic antidepressant, induces food craving and body weight gain in patients. The present study investigated the effects of chronic treatment with CMI on total food intake, macronutrient selection, and body weight gain in rats. Male Wistar rats were maintained on a dietary self-selection regime with separate sources of protein, fat and carbohydrate. Animals received i.p. injections of CMI (0, 3, 10, 30 mg/kg) during 27 consecutive days. Food consumption and body weight were recorded daily and results were calculated as average of three consecutive days, namely during pre-treatment (3 d before pharmacological treatment), treatment (7th-9th; l6th-l8th and 25th-27th days), and post-treatment (28th-33rd days). Results showed that CMI (30 mg/kg) significantly decreased energy intake during all treatment period, an effect that was related to a decrease in both carbohydrate-rich diet intake and body weight gain. At dose of 3 mg/kg CMI increased the total energy intake in the 16th-18th days, suggesting an apparent biphasic effect of chronic treatment with CMI on caloric intake. Chronic administration with CMI (27 d) did not alter protein-rich or fat-rich diet consumption. The main result of this study indicated that chronic treatment with CMI decreases rather than increase food consumption and body weight gain in rats exposed to a macronutrient self-selection procedure.